ثنائية النص /العرض من النظرية الدرامية الكلاسيكية إلى نظرية العرض المسرحي - كعب, حاتم (جامعة الوادي - University of Eloued, 2022)
بعد أن صرح، برتولت بريخت(( bertolt brecht، -1898-1956م، في بديات القرن الماضي، بأطروحاته النظرية في المسرح، سواء في كتابه" الأرغانون الصغير"، أو في غيره من مؤلفاته، والتي حاول من خلالها الخروج عن أصول الدراما الأرسطية، بدأت ثنائية العرض / النص، تشغل القائمين على المشهد المسرحي العالمي، وتطرح على نحو من الصراع والتضاد، وبدأ كل طرف من أطراف هذه الثنائية يحشد الأنصار، ويرصد الحجج والمبررات للسيطرة على المشهد المسرحي العالمي، كما بدأ التساؤل المفصلي يتكرر: هل حان الوقت لسقوط النظرية الدرامية الأرسطية، والتي هيمنت على تاريخ المسرح العالمي منذ نشأته الأولى عند الإغريق؟ وهل أذن المسرح بالخروج عليها؟ أم أن هذه النظرية لها من التقاليد الفنية، ومن الأعراف النقدية، ومن الأنصار، ما يحول دون ذلك؟ وهل يمكن لنظرية العرض المسرحي-حديثة النشأة-، والتي ولدت مع مقولات بريخت، أن تنسف هذا الإرث النظري الدرامي الرصين، الذي أسس له أرسطو قبل قرون طويلة، في كتابه "فن الشعر"؟ وبعد كل هذا، هل من فسحة لتعايش النظرتين، والسير معا دون صدام؟ وعليه نقول: إن هذه الدراسة تحاول طرح إشكالية نقدية مسرحية، تتوزع عبر جملة من الأسئلة أهمها: هل يمكن ضم المسرح ضمن الحقل الأدبي، أم هو أوسع من أن يدخل تحت هذا التصنيف؟،هل يمكن حصر الظاهرة المسرحية، في كونها نصوصا مسرحية كتبت لكي تمثل فقط؟، هل المسرح عروض ماتعة في المقام الأول؟ هل الظاهرة المسرحية نص فقط، أم عرض فقط؟، هل النص هو مركز الظاهرة المسرحية، أم أن هناك أشياء أخرى تقاسمه هذه المركزية؟ After Bertolt Brecht (1898-1956), in the early part of the last century, stated his theoretical propositions in the theatre, whether in his book "The Little Argon" or in other of his works, through which he tried to depart from the origins of Aristotelian drama. The duality of the show/text started to occupy the people in charge of the world theatrical scene. It was displayed in a conflictual and contradictory manner within which each party of this duality started to mobilize supporters and build-up arguments and justifications to control the world theatrical scene. So has the specific enquiry started to become more frequent: Is it time for the fall of the Aristotelian dramatic theory which has dominated the world’s theater history since its inception by the Greeks? Has the theatre allowed us to go out of it? Or does this theory have the artistic traditions, critical customs, and enough advocates that prevent its fall? And could the newborn stage-show theory that emerged with Brecht’s quotes eradicate this solid theoretical legacy that Aristotle established centuries ago in his book The Art of Poetry? After all, is there room for the two theories to coexist toghether without conflict? According to the aforementioned questions, wemaysay: This studyattempts to discuss a criticaltheatricalproblem, whichisdistributedthroughanumber of questions, the most important of which are: Can theaterbeincludedwithin the literaryfield, or isittoobroad to fallunderthis classification? Can the theatricalphenomenonbelimited to theatricaltextswritten to representonly? Are theatresprimarily fun shows? Is theatricalphenomenon a text-only, or only a presentation? Is the text the centre of the theatricalphenomenon, or are thereotherthingsshared by thiscentrality?
مقال
Keywords: المسرح ; المسرحية ; العرض ; النظرية الدرامية الكلاسيكية ; نظرية العرض المسرحي